2000
DOI: 10.1038/sj.onc.1203705
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E4orf4 protein interacts with both Bα and B′ subunits of protein phosphatase 2A, but E4orf4-induced apoptosis is mediated only by the interaction with Bα

Abstract: Adenovirus E4orf4 protein is a multifunctional viral regulator, which is involved in down regulation of virally-modulated signal transduction, in control of alternative splicing of viral mRNAs, and in induction of apoptosis in transformed cells. It has been previously shown that E4orf4 interacts with protein phosphatase 2A through the phosphatase Balpha subunit. It was further shown that PP2A is required for performing the various E4orf4 functions. We report here that E4orf4 interacts with multiple isoforms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 46 publications
2
86
1
Order By: Relevance
“…It also relies on the finding that E4orf4-induced cell death requires an interaction between E4orf4 and an active PP2A, containing both catalytic and regulatory subunits (22,23). The mutants selected by this protocol may be deficient in their ability to bind either E4orf4 or the PP2A-AC heterodimer.…”
Section: Selection For Cdc55 Mutants That Cannot Mediate E4orf4mentioning
confidence: 99%
See 2 more Smart Citations
“…It also relies on the finding that E4orf4-induced cell death requires an interaction between E4orf4 and an active PP2A, containing both catalytic and regulatory subunits (22,23). The mutants selected by this protocol may be deficient in their ability to bind either E4orf4 or the PP2A-AC heterodimer.…”
Section: Selection For Cdc55 Mutants That Cannot Mediate E4orf4mentioning
confidence: 99%
“…We have previously shown that E4orf4 interacts with the PP2A holoenzyme through a direct association with the B␣/B55 subunit (17), and can also bind PP2A complexes containing BЈ/B56 (23). We, and others, have recently shown that the interaction with PP2A complexes that include the B␣/B55, but not the BЈ/B56 subunit, is required for induction of apoptosis by E4orf4 (22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The existence of so many regulatory subunits suggests that the various forms of PP2A have distinct functions. In addition, numerous interactions of PP2A with growth regulatory viral [17][18][19] and cellular 20 proteins have been reported, underscoring its regulatory role.…”
mentioning
confidence: 99%
“…Another viral protein that interacts with PP2A is adenovirus E4orf4. By binding the B subunit in the holoenzyme, E4orf4 induces p53-independent apoptosis (Kleinberger and Shenk, 1993;Marcellus et al, 2000;Shtrichman et al, 1999Shtrichman et al, , 2000. PP2A also associates with numerous cellular proteins that are involved in growth regulation Virshup, 2000).…”
Section: Introductionmentioning
confidence: 99%